Sosialisasi Permainan Pickleball di Kabupaten Lombok Timur Tahun 2023 - Hulfian, Lalu; Jamaludin, Jamaludin; Kusuma, Lalu Sapta Wijaya; Taufik, Kurnia; Primayanti, Intan (Jurnal Surya, 2023)
The purpose of this Community Service (PKM) activity is to introduce and socialize the sport of pickleball.  Pickleball is a sport that is relatively new to develop in Indonesia. Even the sport is not yet known at all in several regions of Indonesia, including one of them in the East Lombok district, West Nusa Tenggara. The game uses rackets such as badminton, court tennis, and table tennis. Although the characteristics of pickleball sports games are almost the same or similar to sports that use rackets. This socialization was carried out to court tennis, badminton, and table tennis players in the East Lombok region, where in the material there were basic technical materials, playing techniques, rules, and refereeing procedures. The method of implementing this activity is divided into three stages, namely (1) theoretical explanation and practice of basic techniques and playing techniques, (2) practice of refereeing procedures in pickleball, and (3) game techniques. The results of this PKM show that partners who participate in this PKM can understand and practice basic techniques, and playing techniques, and can apply refereeing procedures by the standard rules of the pickleball sports federation.